9-(4y-8)=9-5y

Simple and best practice solution for 9-(4y-8)=9-5y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-(4y-8)=9-5y equation:


Simplifying
9 + -1(4y + -8) = 9 + -5y

Reorder the terms:
9 + -1(-8 + 4y) = 9 + -5y
9 + (-8 * -1 + 4y * -1) = 9 + -5y
9 + (8 + -4y) = 9 + -5y

Combine like terms: 9 + 8 = 17
17 + -4y = 9 + -5y

Solving
17 + -4y = 9 + -5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '5y' to each side of the equation.
17 + -4y + 5y = 9 + -5y + 5y

Combine like terms: -4y + 5y = 1y
17 + 1y = 9 + -5y + 5y

Combine like terms: -5y + 5y = 0
17 + 1y = 9 + 0
17 + 1y = 9

Add '-17' to each side of the equation.
17 + -17 + 1y = 9 + -17

Combine like terms: 17 + -17 = 0
0 + 1y = 9 + -17
1y = 9 + -17

Combine like terms: 9 + -17 = -8
1y = -8

Divide each side by '1'.
y = -8

Simplifying
y = -8

See similar equations:

| -3+n+2n=9 | | x*6=13 | | 5(a+-3)-a=23 | | 3x-15=3x+18 | | 7.41x-3.69=9.82 | | 140-5x=22x+23 | | 9(-9-3)=12(-9) | | 7a=39 | | 51.56-29.28x=47.78x-68.82 | | x*6-55=x*4-7 | | 9x+5-4x=-16 | | 8x^2-30x+25= | | 3t^3+14t^2+8t=0 | | 3y-5y=-50 | | 8x^4+16x^3-x-2=0 | | 13-8x=51-15x | | 30.76+x=25+x | | 2(n-20)=-2 | | 10x+6y=20.10 | | 4a-5c-7a+2c= | | 1-7p=1-p | | 7x^4-6x^3+27x^2-24x-4=0 | | 4(m-3)-4(8m+8)=-29(m+2)+6 | | 4y+15=5y-11 | | 3(5c+1)-12=13c+12 | | 7(y-2)=6y | | (3x-5)/4=5 | | .03x+1.2x=1.23 | | 2d+.2=3.6 | | 30.76x=25x | | 77=6x+11+3x | | -9(y+1)=-8y-2 |

Equations solver categories